2007
DOI: 10.1038/nature06205
|View full text |Cite
|
Sign up to set email alerts
|

Interferon modulation of cellular microRNAs as an antiviral mechanism

Abstract: RNA interference through non-coding microRNAs (miRNAs) represents a vital component of the innate antiviral immune response in plants and invertebrate animals; however, a role for cellular miRNAs in the defence against viral infection in mammalian organisms has thus far remained elusive 1 . Here we show that interferon beta (IFNβ) rapidly modulates the expression of numerous cellular miRNAs, and that eight of these IFNβ-induced miRNAs have sequence-predicted targets within the hepatitis C virus (HCV) genomic R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
691
4
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 804 publications
(739 citation statements)
references
References 26 publications
36
691
4
2
Order By: Relevance
“…We demonstrated that IFN-␣/␤ treatment of monocytes induced the expression of anti-HIV miRNAs ( Figure 2C). This finding supports the studies by others 36,43,44 showing that IFN-␣/␤ is the potent inducer of miRNAs in several cell systems. However, this IFN-mediated anti-HIV innate immunity in monocytes was dampened by morphine treatment (Figure 2C).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We demonstrated that IFN-␣/␤ treatment of monocytes induced the expression of anti-HIV miRNAs ( Figure 2C). This finding supports the studies by others 36,43,44 showing that IFN-␣/␤ is the potent inducer of miRNAs in several cell systems. However, this IFN-mediated anti-HIV innate immunity in monocytes was dampened by morphine treatment (Figure 2C).…”
Section: Discussionsupporting
confidence: 92%
“…A recent study 36 has shown that type I IFNs modulate miRNA expression as an antiviral mechanism. We demonstrated that IFN-␣/␤ treatment of monocytes induced the expression of anti-HIV miRNAs ( Figure 2C).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown previously that miRs can directly target hepatitis C viral RNA to repress viral replication 33 , thus raising the possibility that miRs could similarly repress L1 activity in hypomethylated somatic cells. Furthermore, depletion of three of the main proteins involved in miR biogenesis and miR function (Dicer, DGCR8 and Ago) in different cell types results in significantly increased L1 activity 26,27 .…”
Section: Identification Of Retrotransposition-repressor Mirsmentioning
confidence: 99%